Rare lung diseases I--Lymphangioleiomyomatosis. - Juvet, S; Hwang, D; Downey, G (2006)
The present article is the first in a series that will review selected rare lung diseases. The objective of this series is to promote a greater understanding and awareness of these unusual conditions among respirologists. Each article will begin with a case that serves as a focal point for a discussion of the pathophysiology and management of the particular condition. The first article is on lymphangioleiomyomatosis (LAM); subsequent articles will focus on pulmonary alveolar proteinosis, alpha-1-antitrypsin deficiency and primary ciliary dyskinesia. LAM is a rare, progressive and (without intervention) often fatal interstitial lung disease that predominantly affects women of childbearing age. LAM is characterized by progressive interstitial infiltration of the lung by smooth muscle cells, resulting in diffuse cystic changes of the lung parenchyma. The molecular basis of this disorder has been delineated over the past five years and LAM is now known to be a consequence of mutations in the tuberous sclerosis genes. This knowledge, combined with advances in our understanding of the signalling pathways regulated by these genes, has given rise to potential molecular therapies that hold great promise for treating this devastating disease.